2002
DOI: 10.1002/jcc.10077
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study on the electronic structures of styrene in the Franck‐Condon region

Abstract: The electronic structures of styrene in the Franck-Condon region have been theoretically examined by means of ab initio complete active space self-consistent field (CASSCF) and the second order multireference Møller-Plesset calculations. The optimized structure of styrene in S(0) is planar but the torsional motion of the phenyl group is very floppy. The S(1) state is assigned to the local pi-pi* excitation within the benzene ring. On the other hand, S(2), above S(1) by 0.561 eV, is assigned to a state that res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Finally, we give our perspective of the common feature of the π-conjugated systems polyene and polyynes in the radiationless relaxation of photoisomerization or internal conversion. Up to now, we have examined the photochemistry of typical π-conjugated systems. , Thereby, it is found that the bond alternation of π-conjugated systems is essential for the radiationless relaxation of S 1 −S 0 or S n −S 1 ( n ≥ 2). We will further continue to check if the feature is commonly found in another π-conjugated system by means of ab initio methods.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we give our perspective of the common feature of the π-conjugated systems polyene and polyynes in the radiationless relaxation of photoisomerization or internal conversion. Up to now, we have examined the photochemistry of typical π-conjugated systems. , Thereby, it is found that the bond alternation of π-conjugated systems is essential for the radiationless relaxation of S 1 −S 0 or S n −S 1 ( n ≥ 2). We will further continue to check if the feature is commonly found in another π-conjugated system by means of ab initio methods.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in the previous articles, eight electrons in eight orbitals complete active space self‐consistent field [denoted by (8,8)CASSCF] calculations are proper to discuss the photochemical behavior of styrene in the low‐lying excited states 1, 3. Therefore, we applied (8,8)CASSCF to the allocation of the S 2 /S 1 ‐CIX.…”
Section: Methods Of Calculationsmentioning
confidence: 99%
“…The basis set used in the present calculations is same as the previous one 1, 3. Except for the allocation of the S 2 /S 1 ‐CIX by GAUSSIAN98,4 we used GAMESS program in the present ab initio calculations 5…”
Section: Methods Of Calculationsmentioning
confidence: 99%
See 2 more Smart Citations